Online learning during covid-19 pandemic: students readiness, depression, anxiety and its associated factors among medical students in Universiti Sains Malaysia - Mukhtar, Nurfatiniah (2023)
Background: Online learning can affect students' mental health. This study aimed to determine online learning readiness and associated factors of depression and anxiety during the Covid-19 pandemic among undergraduate medical students, Universiti Sains Malaysia. Methods: A cross-sectional study was conducted from February 2022 to June 2022 among 258, undergraduate preclinical medical students, by using an online Google form questionnaires which include sociodemographic profile, Online Learning Readiness Scale-18 items (OLRS-18) and Depression, Anxiety and Stress Scale-21 (DASS-21). Data was analysed using measure of frequency for depression and anxiety and measure of mean for level of readiness on online learning. Logistic regression analysis was conducted to examine factors associated with depression and anxiety. Results: The findings showed the mean scores for online learning readiness ranged between 3.45 and 4.31, indicating that the students demonstrate low to moderate levels of readiness for online education. The students had high computer/Internet self-efficacy, learning motivation, and self-directed learning while lacked online communication efficacy and learner control. The prevalence of depression and anxiety were 42.7% and 6.6% respectively. Poor and unstable internet access, as well as a wide range of online teaching approaches, were identified as associated factors for depression and anxiety. Conclusions: Undergraduate medical students at USM had a low to moderate level of online learning readiness, with lower scores on communication self-efficacy and learner control. This indicated that online communication self-efficacy and learner control should be emphasised to better prepare students for online learning. Poor and unstable internet connectivity and too many variations in online teaching methods were identified as associated factors for depression and anxiety. This meant that lecturers had to help students with problems connecting to the internet and come up with effective ways to teach online. It also meant that the university had to train more academicians to improve online teaching. The government, telecommunications companies and universities should all help build a nationwide internet infrastructure because online learning has been hard without more investments in internet infrastructure.